IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Dewi gustini lubis; Yufi Latmini Lasari (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2024)
Education involves a dynamic exchange between instructors, students, plus various learning resources with the aim of achieving changes in students' attitudes and thinking patterns. This research focuses on IPS in elementary schools, which is a subject that explores and analyzes Issues within society diverse aspects of life or a collective of both. Currently, that Indonesian government is implementing an independent learning curriculum in education, which guides learning with a differentiated approach, assuming that each student has learning opportunities tailored to their needs and abilities. Differentiated learning adapts learning methods to students' interests, preferences and motivation to increase the achievement of learning outcomes. This research uses the literature study method, which involves gathering information through Reviewing relevant literary theories for the research topic. Data sources consist of reference books and scientific journal articles, involving the process of collecting, reading and recording library data, as well as processing the required information. Research findings show that Applying differentiated learning in social sciences. is very suitable for increasing student potential. here proven Through the improvement of educational results when differentiated knowledge is applied to social studies subjects.